Analysis of Determinants of Hemodialysis Patient Satisfaction in Nursing Services: A Literature Review - Evalatifah Nurhayati; Elis Anggeria; Tiarnida Nababan (Jurnal Keperawatan Priority, 2026)
Patient satisfaction is an essential indicator of the quality of nursing care, particularly among individuals undergoing hemodialysis treatment. This literature review aims to identify the determinants influencing hemodialysis patients' satisfaction with nursing services. Literature searches were conducted through PubMed, ScienceDirect, Scopus, Google Scholar, and ResearchGate for articles published between 2021 and 2025. From a total of 2,967 articles initially identified, nine studies met the inclusion criteria. The analysis revealed two primary factors significantly associated with patient satisfaction: nurses' caring behavior and therapeutic communication. Caring behavior includes empathy, attention, support, and the ability of nurses to meet both physical and emotional patient needs, while therapeutic communication refers to professional interactions that build trust and enhance patient understanding of the care process. Both factors were found to improve patients' perceptions of service quality and promote adherence to hemodialysis treatment. This review highlights the importance of strengthening caring competencies and therapeutic communication skills as key strategies to enhance the quality of nursing care in hemodialysis units.